Myocardial Infarction: The Protective Role of MiRNAs in Myocardium Pathology - Wang, Wei; Zheng, Hao (Frontiers in Cardiovascular Medicine, 2021)
Cardiovascular diseases have been regarded as the leading cause of death around the world, with myocardial infarction (MI) being the most severe form. MI leads to myocardial apoptosis, cardiomyocyte fibrosis, and cardiomyocyte hypertrophy, ultimately leading to heart failure, and death. Micro RNAs (miRNAs) participate in the genesis and progression of myocardial pathology after MI by playing an important regulatory role. This review aims to summarize all available knowledge on the role of miRNAs in the myocardial pathological process after MI to uncover potential major target pathways. In addition, the main therapeutic methods and their latest progress are also reviewed. miRNAs can regulate the main signaling pathways as well as pathological processes. Thus, they have the potential to induce therapeutic effects. Hence, the combination of miRNAs with recently developed exosome nanocomplexes may represent the future direction of therapeutics.